(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2017)
Who are the Gurkhas? The Gurkha Memorial Museum in Pokhara starts out their exhibition of the “Gurkha Story” by exploring this question. The narrative approach connects the Gurkha origin to the events of the 19th century Nepal. In a chronological order, the story unfolds, as we see the Gurkha involve in the two world wars and to the present time. Several mediums have been integrated to express the lives and contributions of the Gurkhas, and through these depictions we see them in a familiar and unfamiliar light, some that are widely recognized and a few that are not so easily seen.